\((x-2) (x-3) - \cfrac{a+1}{a^2}\)=0
\((x-2) (x-3) - \cfrac{a+1}{a^2}=0\)
বা, \((x^2-3x-2x+6) - \cfrac{a+1}{a^2}=0\)
বা, \(\cfrac{(x^2-3x-2x+6)a^2-a-1}{a^2}=0\)
বা, \(a^2x^2-5a^2x+6a^2-a-1=0\)
বা, \(a^2x^2-5a^2x+6a^2-3a+2a-1=0\)
বা, \(a^2x^2-5a^2x+3a(2a-1)+(2a-1)=0\)
বা, \(a^2x^2-ax.5a+(2a-1)(3a+1)=0\)
বা, \(a^2x^2-ax.\{(2a-1)+(3a+1)\}+(2a-1)(3a+1)=0\)
বা, \(a^2x^2-(2a-1)ax-(3a+1)ax+(2a-1)(3a+1)=0\)
বা, \(ax\{ax-(2a-1)\}-(3a+1)\{ax+(2a-1)\}=0\)
বা, \(\{ax-(2a-1)\}\{ax-(3a+1)\}=0\)
বা, \((ax-2a+1)(ax-3a-1)=0\)
\(\therefore \) হয়, \(ax-2a+1=0\)
বা, \(ax=2a-1\)
বা, \(x=\cfrac{2a-1}{a}=2-\cfrac{1}{a}\)
নয়, \(ax-3a-1=0\)
বা, \(ax=3a+1\)
বা, \(x=\cfrac{3a+1}{a}=3+\cfrac{1}{a}\)
\(\therefore\) নির্ণেয় সমাধান \(x=2-\cfrac{1}{a}, 3+\cfrac{1}{a}\)